Sirt6 Regulates the Development of Medullary Thymic Epithelial Cells and Contributes to the Establishment of Central Immune Tolerance - Zhang, Qian; Liang, Zhanfeng; Zhang, Jiayu; Lei, Tong; Dong, Xue; Su, Huiting; Chen, Yifang; Zhang, Zhaoqi; Tan, Liang; Zhao, Yong (Frontiers in Cell and Developmental Biology, 2021)
Although some advances have been made in understanding the molecular regulation of mTEC development, the role of epigenetic regulators in the development and maturation of mTEC is poorly understood. Here, using the TEC-specific Sirt6 knockout mice, we found the deacetylase Sirtuin 6 (Sirt6) is essential for the development of functionally competent mTECs. First of all, TEC-specific Sirt6 deletion dramatically reduces the mTEC compartment, which is caused by reduced DNA replication and subsequent impaired proliferation ability of Sirt6-deficient mTECs. Secondly, Sirt6 deficiency specifically accelerates the differentiation of mTECs from CD80-Aire- immature population to CD80+Aire- intermediate mature population by promoting the expression of Spib. Finally, Sirt6 ablation in TECs markedly interferes the proper expression of tissue-restricted antigens (TRAs) and impairs the development of thymocytes and nTreg cells. In addition, TEC conditional knockout of Sirt6 results in severe autoimmune disease manifested by reduced body weight, the infiltration of lymphocytes and the presence of autoantibodies. Collectively, this study reveals that the expression of epigenetic regulator Sirt6 in TECs is crucial for the development and differentiation of mTECs, which highlights the importance of Sirt6 in the establishment of central immune tolerance.